Review of the genus Metipocregyes Breuning, 1939 with two new combinations and three new species (Coleoptera, Cerambycidae, Lamiinae, Mesosini) - Yamasako, Junsuke; Lin, Mei-Ying (Zootaxa, 2018)
The genus Metipocregyes Breuning, 1939 is reviewed. Hypocacia fruhstorferi Breuning, 1959 and H. wenhsini Yamasako & Chou, 2013 are transferred to Metipocregyes. Three new species of Metipocregyes are described; M. brunneatus sp. nov. from Vietnam, M. holzschuhi sp. nov. from Laos, and M. variabilis sp. nov. from China. With these taxonomic acts, Metipocregyes is comprised of six species and an identification key for them is presented. The habitus, male genitalia, and name-bearing types of all species in this study are figured.